Сутнісні характеристики необоротних активів підприємства - Андрійчук, Ю. А.; Карпенко, Ю. В.; Andreychuk, Y. A.; Karpenko, Y. V. (Видавництво Львівської політехніки, 2017)
Проаналізовано змістове наповнення категорії “необоротні активи” у світовій економічній літературі. Досліджено підходи до трактування необоротних активів підприємства вітчизняних учених. Вивчено тлумачення необоротних активів у нормативно-правовій базі України. Запропоновано авторське визначення категорії “необоротні активи підприємства”. Окреслено перспективи подальших досліджень.

The modern environment of functioning of domestic enterprises is characterized. The listed main factors that occur in the dynamic and changing external environment of the operation of the enterprise in the present. The main parameters for success, as well as stability in financial, investment and production-economic activity are outlined. It is proved that the non-current assets of modern companies play a key role in the stabilization processes. The author's analysis of scientific literary sources suggests that at the present stage of development of the theory and practice of management, the problems of adaptive planning have not yet been sufficiently investigated, practically no scientific and methodological principles of its organization have been developed. The object of the study is the company's non-negotiable assets. The subject of the study is theoretical and methodological provisions on the effective management of non-negotiable assets in the system of effective management of a modern enterprise. The following methods of scientific research have been used to achieve the set goal and to solve certain tasks: analysis - to study the scientific-theoretical and applied base in the field of management of non-current assets; system approach – for building a comprehensive understanding of the essence of non-current assets; grouping method – to identify the systemic influence of factors on the formation of a single category interpretation; method of morphological analysis – to clarify the conceptual-categorical apparatus. The content content of the category "non-negotiable assets" in the world economic literature is analyzed. Comparison of existing scientific developments in Germany, Switzerland, Estonia, Russia and Egypt. The approaches to the treatment of non-current assets of the enterprise of domestic scientists are investigated. The basic directions in the wellknown modern concepts of the concept are determined. The study of the interpretation of noncurrent assets in the normative-legal basis of Ukraine. The author's definition of category "non-negotiable assets of the enterprise" is offered. Thus, the study of scientific literary sources devoted to studying the problems of determining the essence of neobortnyh assets allows to assert the lack of a single vision of this economic category. This discrepancy is followed in international economic thought, scientific developments of domestic economists and the normative and legal basis of Ukraine. Ambiguity and controversy of the views complicate the further study of the management of nonnegotiable assets of the enterprise as an instrument for achieving stability and ensuring the prosperity of national enterprises in today's highly competitive market environment. Further research should be carried out in the direction of studying the composition and structure of non-current assets, the methodology of their accounting and the process of depreciation in order to develop an effective mechanism for managing non-current assets of the enterprise.
The essential characteristics of non-current assets of the company
Keywords: підприємство; активи; необоротні активи; майно; термін корисного використання; enterprise; assets; non-current assets; property; useful life; 658.2